Broad-band study of the Be X-ray binary RX J0520.5-6932 during its outburst in 2024 - Yang, H. N.; Maitra, C.; Vasilopoulos, G.; Haberl, F.; Jenke, P. A.; Karaferias, A. S.; Sharma, R.; Beri, A.; Ji, L.; Jin, C.; Yuan, W.; Zhang, Y. J.; et al. (OUP, 2025)
A new giant outburst of the Be X-ray binary RX J0520.5-6932 was detected and subsequently observed with several space-borne and ground-based instruments. This study presents a comprehensive analysis of the optical and X-ray data, focusing on the spectral and timing characteristics of selected X-ray observations. A joint fit of spectra from simultaneous observations performed by the X-ray telescope (XRT) on the Neil Gehrels Swift Observatory (Swift) and Nuclear Spectroscopic Telescope ARray (NuSTAR) provides broad-band parameter constraints, including a cyclotron resonant scattering feature (CRSF) at $32.2_{-0.7}^{+0.8}$ keV with no significant energy change since 2014, and a weaker Fe line. Independent spectral analyses of observations by the Lobster Eye Imager for Astronomy, Einstein Probe (EP), Swift-XRT, and NuSTAR demonstrate the consistency of parameters across different bands. Luminosity variations during the current outburst were tracked. The light curve of the Optical Gravitational Lensing Experiment (OGLE) aligns with the X-ray data in both 2014 and 2024. Spin evolution over 10 yr is studied after adding Fermi Gamma-ray Burst Monitor data, improving the orbital parameters, with an estimated orbital period of 24.39 d, slightly differing from OGLE data. Despite intrinsic spin-up during outbursts, a spin-down of $\sim$ 0.04 s over 10.3 yr is suggested. For the new outburst, the pulse profiles indicate a complicated energy-dependent shape, with decreases around 15 and 25 keV in the pulsed fraction, a first for an extragalactic source. Phase-resolved NuSTAR data indicate variations in parameters such as flux, photon index, and CRSF energy with rotation phase.
Keywords: Astrophysics - High Energy Astrophysical Phenomena